THE EFFECTIVENESS OF CRIMINAL LAW POLICIES ON RELIGIOUS ABUSE AND BLASPHEMY CRIMES - Yudhi Achmad Bashori (Jurnal Al-Dustur, 2020)
ABSTRACTCriminal law policy is one of the instruments of the rule of law - specifically Indonesia - to realize security and order in the lives of every citizen. One of the crimes that often trigger conflicts between the communities is acts related to religion. This is because anthropologically, Indonesian communitiesare known as religious communities. So that if there is an "offended religious" as a consequence of someone's action, it often leads to mass actions. This article focuses on 2 formulations; they are: how is the criminal law policy on religious abuse and blasphemy in Indonesia? How is the effectiveness of criminal law policy on religious abuse and blasphemy in Indonesia?Methodologically, this article uses a qualitative method that will compare existing law policies with Soerjono Soekanto's theory about factors that influence law enforcement. The data source is taken from several applicable laws, news media, and a descriptive analysis of the author.In conclusion, the government has issued a law policy in the form of ratification of Law no. 1 PNPS of 1965 concerning the Prevention ofReligious Abuse and or Blasphemy. At the same time, the effectiveness of criminal law policies against Religious Abuse and Blasphemy (PPA) criminal acts is considered very useful. However, there are deficiencies in the law awareness factor among the community, which in the practice of law enforcement often results in acts of anarchism that violate other legal instruments.